Discussing area studies through family resemblances -Reflections on the Organization of Research in the Social SciencesDiscussing area studies through family resemblances -Reflections on the Organization of Research in the Social Sciences (2017)
This article starts with a very simple question: How useful are 'area studies' as a specific way of organizing research? To reflect on this problem, the article uses the metaphor of 'family resemblances', proposed by Ludwig Wittgenstein, which is based on the ideas of intertwining and overlapping. It enables us to point out the fact that there are only partial resemblances between the investigations of the various researchers (which can relate to methodology, objects, themes, fieldwork, etc.). In this sense, organizing research consists in bringing together projects and investigations which, despite their irreducible singularity, share with others a certain 'family air', but in no case a common essence. In this context, we will reflect on the relative value of 'area studies' in relation to other classification systems that govern the division of labor in the social sciences, whether in the traditional mode of disciplines or, in the more recent one, specialized fields of studies. © S.A.C.. Tous droits réservés pour tous pays.